Automobile response to road safety barriers upon collision - Quan, Chu Nguyen Anh; Anh, Ly Hung (Vietnam Journal of Mechanics, 2024)
During a collision between an automobile and a road safety barrier, the vehicle will go through many behavior transition phases. This research will focus on determining the behavior of two car models including a sedan car and a pickup truck in collision with two safety road barriers using numerical simulation. This paper will also present images, total force graphs, and velocity graphs throughout the process to evaluate the vehicle's behavior at different impact speeds and angles. It is recognized that at similar impact speeds, collision angles, and barrier types, the pickup truck suffers more damage than the sedan. In addition, the pickup truck colliding with a concrete barrier exhibits the highest force, while the sedan colliding with a W-Beam barrier records the lowest force among the four collision types. Regarding the road safety barrier, the concrete barrier has a shorter force increase/decrease duration than the W-Beam barrier.